Life Harvest - Jocelyn, Ann Henning (Saga Egmont, 2023)
\'Life Harvest\' is a collection of thoughts and reflections from the pen of Ann Henning Jocelyn. Containing both poetry and prose, \'Life Harvest\' offers the reader a gentle and benevolent exploration of the various stages of life. Henning\'s observations are funny, poignant, inspiring, and rooted in love. This book would make a superb gift for anyone who needs a little literary sunshine in their life.